Alliance Skill Development within Canadian First Nations and Aboriginal Counsellor Education - Morrissette, Patrick J.; Gadbois, Shannon (Canadian Journal of Counselling and Psychotherapy, 2007)
EnglishAlthough a focus on counsellor-client alliance is prominent within counsellor education, specific skills that comprise this aspect of the helping process remain nebulous. As such, faculty and students have relied on general guidelines and suggestions regarding the engagement process. Research conducted by Bedi, Davis, and Arvay (2005), however, has been instrumental in reversing this trend and provides an excellent foundation with which to better understand elements essential to the alliance process. This article discusses these findings in relation to Canadian First Nations and Aboriginal (FNA) counsellor education and emphasizes cultural imperatives and practices. Français Non disponible